Pengaruh Pembiasaan Asmaul Husna di Sekolah terhadap Akhlak Bullying Peserta Didik SDN 04 Gambuhan - Khafidotun Nafsiyah; Asmaji Mochtar; Toha Makhsun (Journal on Education, 2025)
This study aimed to investigate the impact of regular Asmaul Husna practice in schools on bullying behavior among students of SDN 04 Gambuhan. Employing a descriptive qualitative approach, this research sought to describe real-world phenomena as they occurred. Data was collected through observation, interviews, and document analysis. The findings indicated a significant positive correlation between the practice of Asmaul Husna and a reduction in bullying behavior. As students engaged more frequently in reciting Asmaul Husna as a form of remembrance (dhikr) and supplication, they exhibited decreased bullying tendencies toward their peers. Moreover, collaborative Asmaul Husna practice fostered a sense of appreciation, happiness, camaraderie, love, and respect among students, contributing to the development of positive character traits and good conduct in their daily lives. Additionally, a significant positive correlation was found between students' attitudes towards Asmaul Husna practice and their academic achievement.